Recovery of chemically degraded polyethyleneimine by a re-modification method: prolonging the lifetime of cation exchange membranes. Issue 20 (9th February 2016) - Zhao, Yan; Tang, Kaini; Liu, Qinqin; Van der Bruggen, B.; Díaz, Arcadio Sotto; Pan, Jiefeng; Gao, Congjie; Shen, Jiangnan
Abstract : Recovery of chemically degraded cation exchange membranes in a cyclic process. Abstract : Selectivity for monovalent cations is an important property of cation exchange membranes (CEMs). The cation exchange membranes of the CSO modified with polyethyleneimine type have a higher selectivity for monovalent cations than the multivalent cations. Unfortunately, the loss of selectivity for these kinds of CSO seems to be unavoidable due to fouling and degradation of polyethyleneimine groups. In this situation, a "re-modification" technique was developed for recovery of fouled CSO, activating the fouled CSO by methanol and a sulfuric acid solution with ultrasonic vibration, followed by a layered surfacial electro-deposition method to prolong the lifetime of cation exchange membranes. A series of electrodialysis experiments for Na + /Ca 2+ separation was performed for evaluating and comparing the monovalent cation selectivity of the samples. The restoration of the surface and cross section morphology after "re-modification" was demonstrated by attenuated total reflectance Fourier transform infrared spectroscopy (ATR-FTIR), X-ray photoelectron spectroscopy (XPS) and scanning electron microscopy (SEM). As a result of the re-modification method the membranes with chemically degraded polyethyleneimine were again made functional. The ion exchange groups of the CSO modified with polyethyleneimine were successfully recovered, giving the membrane a high permselectivity again.